Empowering Islamic Bank Customers in the Digital Age: The Impact of Financial Literacy on Satisfaction and Marketing Perception - Fifi Afiyanti Tripuspitorini; Setiawan; Fathur Imam Fadhilah; Fizar Muhammad Tribuana (Journal of Islamic Economics and Business, 2024)
This research aims to analyze the role of financial literacy in increasing customer satisfaction with Islamic bank marketing strategies in the digital era. The development of digital technology has changed the landscape of the banking industry, including the implementation of digital service-based marketing strategies. Financial literacy is an important factor in helping customers understand banking products and services, especially in the context of compliance with sharia principles. This research uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method through the SmartPLS application. The research sample consisted of 174 respondents who are users of Islamic bank digital services in Indonesia. The results showed that financial literacy has a positive and significant effect on customer satisfaction but has no direct effect on perceptions of digital marketing strategies. In addition, customer satisfaction is proven to fully mediate the relationship between financial literacy and perceptions of digital marketing strategies of Islamic banks.